Narrar al sodomita: fuentes de archivo y construcción de biografías nefandas del Reino de Valencia en la Edad Moderna. - NAVARRO MARTÍNEZ, JUAN PEDRO (Scripta)
In this article we aim to study the sources we can use to reconstruct the biographies of those accused of sodomy in the Kingdom of Valencia in the Modern Age; the problems faced when dealing with the material from the "sodomite" archive; the possibilities of applying different methods such as small-scale analysis and prosopography as well as reporting on potential uses of both the source and these methodological tracks through the case study.